Diet and dietary patterns during pregnancy in nulliparous women in Ireland: a longitudinal cohort study - DACACH FERNANDEZ MARCHI, JAMILE (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2020)
Background: The impact of maternal diet in pregnancy, for both the mother and baby, has been widely documented. Much of the research on diet in pregnancy has focused on the relationship between single nutrients and maternal and neonatal outcomes. However, more recent studies have demonstrated the need to study diet as a whole. Aim: To identify the diet, dietary patterns, and physical activity levels of nulliparous women during pregnancy, analyse associations with pre-pregnancy and pregnancy factors, and explore associations with pregnancy, birth, neonatal and postpartum outcomes. Design: Longitudinal quantitative study. Setting: One large maternity hospital site in Ireland. Methods: Site hospital and university ethical approval were granted. Eligible women were nulliparous, aged 18 or over, and able to read and understand English sufficiently to complete the Maternal health And Maternal Morbidity in Ireland surveys, in early pregnancy and at 3 months postpartum. A 'Diet and Physical Activity survey' was developed, validated and tested for reliability, and administered in the third trimester of pregnancy. Dietary adequacy, balance, quality assessed according to four dietary methods: the Alternate Healthy Eating Index for pregnancy in Ireland (AHEI-P (Ireland)), k-means cluster analysis, adequacy of all macronutrients and Protein:Non-protein (P:NP) ratio. Sample: A total of 872 nulliparous women were recruited during early pregnancy, 557 of whom completed all three surveys and had a dietary intake classified as 'plausible'. Results: Pre-pregnancy predictors of dietary pattern/quality in need of improvement during pregnancy were: being aged ≤29 years (AOR 3.3, 95% CI 1.9-5.9, p=0.000) (cluster analysis), being educated to Leaving Certificate/vocational level (AOR 2.5, 95% CI 1.5-4.2, p=0.001) (cluster analysis), not exercising (AOR 2.5, 95% CI 1.4-4.5, p=0.003) (cluster analysis), never being satisfied with body image (AOR 2.0, 95% CI 1.2-3.3, p=0.005) (cluster analysis), being overweight (AOR 2.1, 95% CI 1.3-3.3, p=0.001) (AHEI-P (Ireland)), reading food labels sometimes (AOR 2.0, 95% CI 1.3-3.1, p=0.002) (AHEI-P (Ireland)) and (AOR 2.4, 95% CI 1.3-4.4, p=0.003) (cluster analysis) or never (AOR 2.3, 95% CI 1.2-4.3, p=0.013) (AHEI-P (Ireland)) and (AOR 4.9, 95% CI 2.3-10.5, p=0.000) (cluster analysis) and not taking supplements (AOR 1.9, 95% CI 1.3-2.8, p=0.001) (AHEI-P (Ireland)). Pregnancy predictors of dietary pattern/quality during pregnancy were: being overweight pre-pregnancy (AOR 2.3, 95% CI 1.5-3.5, p=0.000) and having food cravings during pregnancy (AOR 0.6, 95% CI 0.4-0.8, p=0.003). According to cluster analysis, predictors of dietary pattern/quality during pregnancy, for amount of time spent walking per week were: being aged ≤29 years (AOR 3.3, 95% CI 1.9-5.9, p=0.000), having Leaving Certificate/vocational level education (AOR 2.6, 95% CI 1.5-4.5, p=0.001), smoking (AOR 5.1, 95% CI 1.5-17.2, p=0.008), having stopped drinking alcohol during pregnancy (AOR 1.9, 95% CI 1.1-3.4, p=0.024), walking for less <150 minutes (AOR 1.6, 95% CI 1.1-2.7, p=0.043) or not walking (AOR 4.2, 95% CI 2.1-8.6, p=0.000) and vomiting during pregnancy (AOR 2.5, 95% CI 1.6-3.8, p=0.000). When exercise was assessed using the variable for moderate physical activity time per week, the predictors of dietary pattern/quality during pregnancy were: doing moderate exercise for <150 minutes (AOR 2.8, 95% CI 1.1-7.1, p=0.033) and doing no moderate physical activity (AOR 6.9, 95% CI 2.8-17.3, p=0.000) and vomiting during pregnancy (AOR 2.3, 95% CI 1.5-3.6, p=0.000). Women more likely to initiate breastfeeding had MSc or PhD level education (AOR 2.7, 95% CI 1.3-5.4, p=0.006) (AHEI-P (Ireland)) and (AOR 2.8, 95% CI 1.4-5.7, p=0.004) (cluster analysis) and were non-Irish (AOR 2.7, 95% CI 1.2-4.7, p=0.004) (AHEI-P (Ireland)) and (AOR 2.4, 95% CI 1.2-4.7, p=0.010) (cluster analysis). Women less likely to initiate breastfeeding were aged ≤29 years old (AOR 0.4, 95% CI 0.2-0.8, p=0.003) (AHEI-P (Ireland)), educated to Junior Certificate level or less (AOR 0.2, 95% CI 0.1-0.8, p=0.021) (AHEI-P (Ireland)) and (AOR 0.2, 95% CI 0.1-0.9, p=0.041) (cluster analysis), Leaving Certificate/vocational level (AOR 0.3, 95% CI 0.2-0.5, p=0.000) (AHEI-P (Ireland)) and (AOR 0.3, 95% CI 0.2-0.6, p=0.000) (cluster analysis) and were in the diet that needed improvement group (AOR 0.5, 95% CI 0.3-0.8, p=0.004) (AHEI-P (Ireland)) and (AOR 0.3, 95% CI 0.2-0.5, p=0.000) (cluster analysis). Women more likely to be breastfeeding at 3 months postpartum were sometimes satisfied with their body image (AOR 5.2, 95% CI 1.9-14.5, p=0.002) (AHEI-P (Ireland)) and (AOR 5.0, 95% CI 1.8-14.0, p=0.002) (cluster analysis). Women less likely to be breastfeeding at 3 months postpartum were aged ≥35 years (AOR 0.5, 95% CI 0.2-0.9, p=0.015) (AHEI-P (Ireland)) and (AOR 0.5, 95% CI 0.3-0.9, p=0.043) (cluster analysis), educated to leaving certificate/vocational level(AOR 0.4, 95% CI 0.2-0.8, p=0.004) (AHEI-P (Ireland)) and (AOR 0.5, 95% CI 0.3-0.9, p=0.019) (cluster analysis), or had a diet during pregnancy that needed improvement (AOR 0.6, 95% CI 0.4-0.9, p=0.039) (AHEI-P (Ireland)) and (AOR 0.4, 95% CI 0.3-0.7, p=0.000) (cluster analysis). There was no statistically significant association found between any of the four dietary methods used to assess diet during pregnancy and outcomes: gestational length, infant weight at birth, postpartum depression and postpartum anxiety. Participants whose P:NP ratio were below the median were statistically less likely to birth spontaneously in comparison to women who were in the above the median for P:NP ratio group in the univariate logistic regression analysis (OR 0.7, CI 95% 0.4-0.9, p=0.037) however P:NP ratio lost its statistical significance when brought to a multinomial multivariable model. Conclusion: Even highly educated, older pregnant women also need some improvements in their diet and lifestyle during pregnancy. Further studies are needed to better understand the diet-disease relationship as diet during pregnancy might be one of the most powerful tools to start ending cycles of disparities and diseases.
APPROVED
Keywords: Diet; Dietary patterns; Physical activity; Pregnancy